2017
DOI: 10.1002/slct.201601765
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of Magnetic Graphene Oxide Modified with 8‐Hydroxyquinoline for Extraction and Preconcentration of Trace Heavy Metal Ions

Abstract: In the present paper for the first time, magnetic graphene oxide (GO‐Fe3O4) was modified with well‐known ligand 8‐hydroxyquinoline, as a new functional group, for simultaneous separation/pre‐concentration of Cd(II) and Pb(II) ions. The experiments and the optimization of variables affecting separation/preconcentration were designed, using the response surface methodology (BBD). In the optimized conditions, the limit of detection (LOD) was 0.09 ng mL–1 and 0.27 ng mL−1 for Cd(II) and Pb(II), respectively; furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…It was concluded that after functionalization with 8-HQ, the GO/Fe 3 O 4 nanoparticles could be used for the extraction of cadmium and lead ions from complex matrices with high selectivity. Compared with the non-functionalized GO/Fe 3 O 4 sorbent, the magnetic 8-HQ modified GO nanocomposite exhibited higher adsorption capacities towards the target analytes [98].…”
Section: Multielement Extraction With Graphene-oxide-derived Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was concluded that after functionalization with 8-HQ, the GO/Fe 3 O 4 nanoparticles could be used for the extraction of cadmium and lead ions from complex matrices with high selectivity. Compared with the non-functionalized GO/Fe 3 O 4 sorbent, the magnetic 8-HQ modified GO nanocomposite exhibited higher adsorption capacities towards the target analytes [98].…”
Section: Multielement Extraction With Graphene-oxide-derived Materialsmentioning
confidence: 96%
“…Other compounds that have been used for the functionalization of graphene oxide for the extraction of metal ions are multi-walled carbon nanotubes (MCNTs) [97], 8-Hydroxyquinoline (8-HQ) [98], glycine [99], and 1,5-bis(di-2-pyridil)methylene thiocarbonhydrazide (DPTH) [100].…”
Section: Multielement Extraction With Graphene-oxide-derived Materialsmentioning
confidence: 99%
“…Dahaghin et al [90,91] proposed two different methods regarding the usage of mGO in MSPE. The first one dealt with the determination of trace amounts of Cd(II), Pb(II) and Cu(II) ions by FAAS by utilizing a modified mGO with 2-mercaptobenzothiazole.…”
Section: Applications Of Go-fe 3 Omentioning
confidence: 99%
“…A number of separation methods for determining trace metal have gained high attention, and these methods include homogeneous liquid-liquid extraction [10,11], liquid-liquid extraction [12], ion exchange [13], and Solid Phase Extraction (SPE) [14]. SPE procedure is superior to other procedures due to its rapidity, simplicity, low cost, exibility, high preconcentration factor, its use in combination with di erent detection techniques in on-or o -line modes, consumption of low organic solvent volume, and short extraction time for sample preparation [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%